KANDUNGAN KLOROFIL TANAMAN KANGKUNG AIR (IPOMOEA AQUATICA) AKIBAT PEMBERIAN LOGAM KADMIUM (CD) PADA BERBAGAI KONSENTRASI - MONITA, RISCA (LenteraBio: Berkala Ilmiah Biologi, 2013)
This research aimed to description the chlorophyll content, the metal cadmium accumulations in the leaves, and the growth of water spinach resulting from the furnishing of cadmium metal with various concentrations, detention time, and the interaction between the two treatments. The research was conducted in the Green House Faculty Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Surabaya using a randomized block design (RAK). Cadmium metal concentrations used were 0 ppm, 8 ppm, 12 ppm, 16 ppm, and 20 ppm, with a detention time for 7 and 14 days. Parameters observed chlorophyll content, accumulation of cadmium in leaves of metal, and water spinach plant growth. Data were then analyzed using 2-way ANOVA and Duncan test continued with a significance level of 0,05. Results showed that giving with a concentration of cadmium metal and different detention time can affect the levels of chlorophyll, metals cadmium accumulation in the leaves, and Ipomoea aquatica Forsk growth. The smallest leaf chlorophyll content indicated on providing metal concentration of 16 ppm, and 20 ppm with detention time of 14 days. The mean greatest metal accumulation in leaves was shown at a concentration of 12 ppm, 16 ppm, and 20 ppm which is equal to 6.357 ppm, 6.765 ppm and 6.468 ppm. Giving a concentration of 20 ppm with a 14-day detention time showed the smallest end of the weight is 34.57 grams.   Key words: kadmium concentration; detention time; chlorophyll content; metals kadmium accumulation; growth water spinach